Journal of Materials Science: Materials in Energy - Lee, Jung-Kun.; Wilkening, Martin R.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
Materials science plays a pivotal role in establishing a sustainable society by developing eco-friendly materials and technologies, ensuring resource efficiency, and minimizing environmental impact throughout the product lifecycle. In particular, materials science is crucial in advancing energy science and technology by enabling the development of efficient energy storage systems, lightweight and durable materials for renewable energy devices, and novel materials for energy conversion processes such as photovoltaics and fuel cells. Journal of Materials Science: Materials in Energy welcomes original articles, comprehensive reviews, and perspectives on all aspects of energy-related materials research. The journal focuses on novel understanding of structure-process-property relations in the context of electronic, optical, electrochemical, thermoelectric, magnetic, and piezoelectric properties. Topics will include, but are not limited to energy harvesting, organic and inorganic photovoltaics, batteries, supercapacitors, fuel cells, hydrogen generation and storage, thermoelectric devices, water splitting, photocatalysis, solar fuels, solar-thermal conversion, magnetocalorics, piezoelectronics, energy transmission, CO2 capture/utilization, sustainable and green materials, and recovery and recycling of energy materials.
Keywords: Materials; Catalysis; Force and energy; Materials; Nanotechnology; Materials science; Materials for Energy and Catalysis; Materials for Devices; Nanotechnology; Materials Science